Classification of the ecological status of volcanic lakes in Central Italy - Daria VAGAGGINI; Marco SEMINARA; Luciana MASTRANTUONO; Ornella FERRARA; Marcello BAZZANTI; Fiorenza G. MARGARITORA (Journal of Limnology, 2003)
A synthesis is made of biological data collected in the last three decades on five volcanic lakes in Central Italy with the aim of evaluating their environmental status by means of biological parameters related to zooplankton, littoral and profundal zoobenthos frequently used to detect water quality changes in lakes. A number of bioindicators and bioindices were selected for this purpose, as far as possible following an integrated approach using information drawn from physical and chemical variables. Our results allowed the lakes to be classified according to their biological quality level, which proved to be in good agreement with physical and chemical diagnoses. Lake Bracciano exhibited the best environmental quality, due to the presence of a ring waste water collecting system, to its large size and depth, and to its strong hydrodynamism. Lake Martignano followed, with some symptoms of stress in the hypolimnion due to a marked summer deoxygenation. Oxygen depletion in the profundal characterized also Lake Vico, which showed a mesotrophic condition in the sixties, and 20 years later now shows clear signs of increased trophy (meso-eutrophy). Lake Albano seemed meso-eutrophic with total absence of fauna below a depth of 120 m due to a meromictic status. Finally Lake Nemi, exposed to domestic wastes in the 70s, suffered a heavy eutrophication with dramatic algal blooms and fish kills. Following the diversion of discharges that occurred in the early 90s, today this lake is characterized by the partial improvement of many ecological features. The need for integration between physical and chemical analyses and biological data in order to obtain a reliable evaluation of lake environmental quality is stressed, especially as far as routine implementation in managing and recovery procedures is concerned.